Disruptive Therapy Using a Nonsurgical Orthodontic Airway Plate for the Management of Neonatal Robin Sequence: 1-Year Follow-up. (June 2023) - Choo, HyeRan; Galera, Rhona I.; Balakrishnan, Karthik; Lin, Hung-Fu C.; Ahn, HyoWon; Lorenz, Peter; Khosla, Rohit K.; Profit, Jochen; Poets, Christian F.; Lee, Janice S.
We recently published the 3-month follow-up of 2 neonates with Robin sequence whose mandibular hypoplasia and restricted airway were successfully treated with an orthodontic airway plate (OAP) without surgical intervention. Both infants were successfully weaned off the OAP after several months of continuous use. We present the course of OAP treatment in these patients with a focus on breathing, feeding, and facial growth during their first year of life. Both infants demonstrated stable mandibular projection, resolution of obstructive sleep apnea, and normal development.